2015
DOI: 10.1039/c5nr01496d
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanowire interactions with primary human alveolar type-II epithelial cell secretions: contrasting bioreactivity with human alveolar type-I and type-II epithelial cells

Abstract: Inhaled nanoparticles have a high deposition rate in the alveolar units of the deep lung. The alveolar epithelium is composed of type-I and type-II epithelial cells (ATI and ATII respectively) and is bathed in pulmonary surfactant. The effect of native human ATII cell secretions on nanoparticle toxicity is not known. We investigated the cellular uptake and toxicity of silver nanowires (AgNWs; 70 nm diameter, 1.5 μm length) with human ATI-like cells (TT1), in the absence or presence of Curosurf® (a natural porc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 26 publications
1
30
2
Order By: Relevance
“…Alone, SP-A and SP-D were previously shown to increase the uptake of magnetite nanoparticles by murine alveolar macrophages (Ruge et al, 2011, Ruge et al, 2012), while Kendall et al showed increased uptake of polystyrene nanoparticles by murine alveolar macrophages and dendritic cells in the presence of SP-D alone (Kendall et al, 2013). In contrast, in our own work, alveolar type II cell secretions reduced AgNW bioreactivity with TT1 cells by reducing their uptake, possibly involving specific binding of SP-A/D to the AgNWs (Sweeney et al, 2015), which we have found induces AgNW agglomeration (Theodorou et al, 2015a). Whether this scenario would be the same for ZnONWs remains to be established.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…Alone, SP-A and SP-D were previously shown to increase the uptake of magnetite nanoparticles by murine alveolar macrophages (Ruge et al, 2011, Ruge et al, 2012), while Kendall et al showed increased uptake of polystyrene nanoparticles by murine alveolar macrophages and dendritic cells in the presence of SP-D alone (Kendall et al, 2013). In contrast, in our own work, alveolar type II cell secretions reduced AgNW bioreactivity with TT1 cells by reducing their uptake, possibly involving specific binding of SP-A/D to the AgNWs (Sweeney et al, 2015), which we have found induces AgNW agglomeration (Theodorou et al, 2015a). Whether this scenario would be the same for ZnONWs remains to be established.…”
Section: Discussioncontrasting
confidence: 87%
“…The exact mechanisms of increased intracellular uptake efficiency after surfactant coating of NPs remain to be investigated in detail. On the one hand, this increase could be due to the reduction in the agglomeration state of ZnONWs following surfactant coating (Figure 3b), as size-dependent uptake of other nanomaterials has been previously observed with TT1 cells (Sweeney et al, 2015). On the other hand, the formation of a lipid shell around the particles (Figure 2n) could have caused an enhanced particle interaction with the cell membrane.…”
Section: Discussionmentioning
confidence: 60%
“…There is growing evidence that AgNPs and AgNWs can enter epithelial cells, interstitial sites, airway smooth muscle cells, the vascular endothelium, and the pleural membrane. 1012 Another aspect is that interaction of nanoparticles with lung lining fluid containing pulmonary surfactant is known to influence uptake of nanowires by alveolar epithelial cells 13 and also the aggregation of nanowires for clearance by alveolar macrophages. 14 Moreover, the effect of AgNWs on the trafficking or production of surfactant proteins such as surfactant protein D (SP-D) is unclear.…”
mentioning
confidence: 99%
“…In addition, the safety issue that could arise from industrial use of nanomaterial-based conductors should be addressed. There are ongoing studies on the toxicity of the nanomaterials themselves [233][234][235][236] and potential exposure to nanomaterials as a result of them being released from products has been very recently investigated. [187] STICs can be promising candidates because most of the hydrogels are biocompatible and are conformal to human body parts, cells, and tissues down to the molecular scale.…”
Section: Challenges and Outlookmentioning
confidence: 99%